The Neuroanatomy of the Reticular Nucleus Locus Coeruleus in Alzheimer’s Disease - Giorgi, Filippo S.; Ryskalin, Larisa; Ruffoli, Riccardo; Biagioni, Francesca; Limanaqi, Fiona; Ferrucci, Michela; Busceti, Carla L.; Bonuccelli, Ubaldo; Fornai, Francesco (Frontiers in Neuroanatomy, 2017)
Alzheimer’s Disease (AD) features the accumulation of -amyloid and Tau aggregates, which deposit as extracellular plaques and intracellular neurofibrillary tangles (NFTs), respectively. Neuronal Tau aggregates may appear early in life, in the absence of clinical symptoms. This occurs in the brainstem reticular formation and mostly within Locus Coeruleus (LC), which is consistently affected during AD. LC is the main source of forebrain norepinephrine (NE) and it modulates a variety of functions including sleep-waking cycle, alertness, synaptic plasticity, and memory. The iso-dendritic nature of LC neurons allows their axons to spread NE throughout the whole forebrain. Likewise, a prion-like hypothesis suggests that Tau aggregates may travel along LC axons to reach out cortical neurons. Despite this timing is compatible with cross-sectional studies, there is no actual evidence for a causal relationship between these events. In the present mini-review, we dedicate special emphasis to those various mechanisms that may link degeneration of LC neurons to the onset of AD pathology. This includes the hypothesis that a damage to LC neurons contributes to the onset of dementia due to a loss of neuroprotective effects or, even the chance that, LC degenerates independently from cortical pathology. At the same time, since LC neurons are lost in a variety of neuropsychiatric disorders we considered which molecular mechanism may render these brainstem neurons so vulnerable.